The Nature of Writing in English as a Foreign Language - بن ايدير, سميرة (Revues faculté des lettres et des langues, 2016)
في الماضي، كان ينظر للكتابة بوصفها انشغال نخبة من  الناس والمتعلمين تعليما عاليا، ولكن هذا الاعتقاد قد تغير لأن  الكتابة أصبحت وسيلة  أساسية يمتلكها كل الناس على اختلاف ألوانهم   و ألسنتهم و تمكن القدرة على الكتابة الناس من مختلف المرجعيات اللغوية والثقافية على التواصل بشكل فعال وفق استخدامات سليمة ، لذا ترقى الجامعات إلى تعليم الطالب (ة) وتمكنه من مهارة الكتابة وسنحاول في هذه الورقة البحثية  أن نقف عند مجموعات من التعريفات التي تصنف الكتابة كمهارة وكنظام قائم بذاته إضافة إلى تحليل طبيعة هذه المهارة وعلاقتها بالمهارات اللغوية الأخرى مع ضرورة الوقوف عند الجوانب التاريخية للكتابة .   Writing  used to  considered the preoccupation of the élite and  the highly cultivated people, but this belief has changed because in the modern global community this ability to write has become an essential tool for people of all kinds and all levels; for instance, writing is used  in composing academic essays, letters              or e-mail messages. In fact, this capacity     to write makes it easy for individuals from different linguistic and cultural backgrounds to communicate effectively. It should be acknowledged that the importance of writing lies not only in the fact that it is used to transfer information but also to transform knowledge to create new knowledge.  It is, therefore , of  primary importance to students in academic settings to master this skill. In this paper, we will undertake to cover in details many definitions of writing as a skill and system. This paper also tries to analyse the nature of the writing skill in English and its interrelation with other skills. It also includes a brief history of the language beside a description of the socio-cultural and cognitive aspects of writing.